2013
DOI: 10.1038/jhg.2013.78
|View full text |Cite
|
Sign up to set email alerts
|

Association of XRCC3 and XRCC4 gene polymorphisms, family history of cancer and tobacco smoking with non-small-cell lung cancer in a Chinese population: a case–control study

Abstract: Single-nucleotide polymorphisms (SNPs) of DNA repair genes have been reported to modify cancer risk. This study aimed to determine SNPs of the DNA repair genes X-ray repair cross-complementing group 3 (XRCC3) and X-ray cross-complementing group 4 (XRCC4) and their association with non-small-cell lung cancer (NSCLC) susceptibility in a Chinese population. A total of 507 NSCLC patients and 662 healthy controls were recruited for genotyping. Epidemiological and clinical data were also collected for association st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The XRCC4 SNP rs1805377 is also associated with poor survival in patients with metastatic prostate cancer [ 146 ]. Carriers of the XRCC4 G-1384T polymorphism (SNP rs6869366) are at a significantly higher risk of developing NSCLC, esophageal, bladder, prostate, gastric, colorectal, and urothelial cancer [ 147 , 148 , 149 , 150 , 151 , 152 ].…”
Section: Core Nhej Factors In Carcinogenesis and Cancermentioning
confidence: 99%
“…The XRCC4 SNP rs1805377 is also associated with poor survival in patients with metastatic prostate cancer [ 146 ]. Carriers of the XRCC4 G-1384T polymorphism (SNP rs6869366) are at a significantly higher risk of developing NSCLC, esophageal, bladder, prostate, gastric, colorectal, and urothelial cancer [ 147 , 148 , 149 , 150 , 151 , 152 ].…”
Section: Core Nhej Factors In Carcinogenesis and Cancermentioning
confidence: 99%
“…Previously, it was shown that frequencies of XRCC4 rs6869366 TG+GG genotypes were higher in patients with autism spectrum disorder than the controls 33 . He et al reported that patients who smoked and carried the XRCC4 rs6869366 G allele had an increased risk for non small cell lung cancer (NSCLC) 34 . In a study conducted on the patients with lung cancer, Hsu et al demonstrated that people with rs 6869366 GT genotype and smoking habit present the highest risk of lung cancer than other groups 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al (2013) conducted a meta-analysis that included five studies, and suggested that rs2075685 and rs6869366 polymorphisms increase the risk of breast cancer. He et al (2013) investigated the association between the XRCC4 gene polymorphisms and the risk of non-small-cell lung cancer and suggested that XRCC4 rs6869366 polymorphism had a significantly increased NSCLC risk. Zhao et al (2013) investigated the association between DSB gene polymorphisms and glioma risk in a Chinese population and found that the XRCC4 rs1805377 polymorphism was associated with an increased risk of gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiologic studies have reported that XRCC4 gene polymorphisms are associated with the risk of several types of cancers, such as colorectal cancer, acute lymphoblastic leukemia, breast cancer, glioma, hepatocellular carcinoma, non-small-cell lung cancer, esophageal cancer and prostate cancer (Bau et al, 2010;Chokkalingam et al, 2011;Zhou et al, 2012;He et al, 2013;Long et al, 2013;Zhao et al, 2013;Fan et al, 2013;Shao et al, 2014). Bau et al (2010) investigated the association between XRCC4 gene polymorphisms and the susceptibility to colorectal cancer, and suggested that XRCC4 rs6869366 polymorphism may contribute to the development of esophageal cancer and may be useful for early detection of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%